2006
DOI: 10.3349/ymj.2006.47.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Comorbidity in Korean Children and Adolescents with Attention-Deficit Hyperactivity Disorder: Psychopathology According to Subtype

Abstract: It is well-known that more than 50% of attention-deficit hyperactivity disorder (ADHD) cases also have comorbid psychiatric disorders. We evaluated the comorbid psychopathology of Korean children and adolescents with ADHD using a standardized diagnostic instrument. The Korean Kiddie-Schedule for Affective Disorders and Schizophrenia-Present and Lifetime Version (K-SADS-PL-K) was administered and completed in 105 patients who had been referred to the outpatient and inpatient clinics at the Samsung Medical Cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
49
1
13

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 26 publications
11
49
1
13
Order By: Relevance
“…26 A Korean study using systemic interview to investigate a clinicreferred sample of 105 ADHD children reported that 66.7% were of combined subtype, 21.0% were of the inattentive subtype, and only one subject (1.0%) was of the hyperactive-impulsive subtype. 27 In our surveyed sample of 182 clinic-referred ADHD children, 68.1% were of combined subtype and 31.8% were of the inattentive subtype. Hyperactive-impulsive subtype children were excluded from the study because none of their caregivers fulfilled the inclusion criteria.…”
Section: Discussionmentioning
confidence: 98%
“…26 A Korean study using systemic interview to investigate a clinicreferred sample of 105 ADHD children reported that 66.7% were of combined subtype, 21.0% were of the inattentive subtype, and only one subject (1.0%) was of the hyperactive-impulsive subtype. 27 In our surveyed sample of 182 clinic-referred ADHD children, 68.1% were of combined subtype and 31.8% were of the inattentive subtype. Hyperactive-impulsive subtype children were excluded from the study because none of their caregivers fulfilled the inclusion criteria.…”
Section: Discussionmentioning
confidence: 98%
“…Esto coincide con otras investigaciones que han hallado hasta el 76,2% de al menos un trastorno comórbido en esta población. En general, la comorbilidad en niños y adolescentes puede explicarse porque es una población que tiene mayor vulnerabilidad bioló-gica y social, ya que es un periodo sensible del neurodesarrollo y porque los antecedentes familiares de trastorno mental y pertenecer a un estrato socioeconómico bajo aumentan el riesgo 5 .…”
Section: Discussionunclassified
“…De los niños remitidos a clínicas psiquiátricas, un 30-50% tiene TDAH 5,6 ; en Colombia, un estudio realizado en un servicio especializado de psiquiatría infantil halló que el 36% tenía este diagnóstico y una comorbilidad total del 94%, las más comunes con el TOD y con los trastornos depresivos 4 ; otra investigación hecha en escolares españoles encontró una comorbilidad total de TDAH del 71%; el 46% de los niños tenían trastorno de ansiedad; el 31%, trastornos de conducta y el 9%, trastornos del ánimo 7 .…”
Section: Introductionunclassified
“…Während im Grundschulalter bis zu 50% der betroffenen Kinder auch ein oppositionelles Verhalten, etwa 23% eine Angststörung [2,24] und gehäuft Schulschwierigkeiten zeigen, weisen Kinder mit Aufmerksamkeitsstörung zu 11% auch eine Dyskalkulie auf [21]. Im Jugendalter wird als komorbide Störung eine bipolare Erkrankung [23] genannt.…”
Section: Diagnostik Und Therapie Von Aufmerksamkeits Störungen Leitthemaunclassified